Adaptive sustainability strategies for old Najaf city: integrating heritage and urban development - Senah, Husam Sachit; Al-Shammari, Rabee Jameel (Al-Nahrain Journal for Engineering Sciences, 2026)
The Old City of Najaf stands out for its unique urban fabric and rich historical heritage, serving as a key destination for religious tourism while hosting worship facilities and housing for seminary students. As both a vibrant religious center and a cultural landmark, it presents a complex urban context that demands a careful balance between residents’ and visitors’ needs. This raises the question of how to adapt sustainability standards to align with the city’s environmental, historical, and cultural dimensions. Using descriptive and analytical methods, including field observations, literature reviews, and expert consultations in urban planning and heritage preservation, the study examines challenges like uncontrolled urban growth, strained infrastructure, and land-use conflicts. Initial findings suggest these issues significantly hinder sustainable development, particularly with growing demand for heritage tourism and Najaf’s role as a hub for religious studies. The study proposes practical strategies to preserve Najaf’s cultural identity, improve residents’ quality of life, and enhance its status as a sustainable heritage tourism destination, boosting its long-term appeal and sustainability.